Kesenjangan Gender Dalam Lapas Kelas II B Bengkulu: (Tentang Fasilitas, Kesehatan, Dan Dukungan Bagi Narapidana Perempuan) - Caca Khairunnisa; Ajah Mas Tati Yarti; Dwi Putri Lestarika (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
This research highlights the gender gap in the Bengkulu Class II B Correctional Institution), especially in terms of providing facilities, health services and support for female prisoners. Prisons are generally designed to meet the needs of the majority of male prisoners, so the specific needs of female prisoners are often overlooked. This study uses a qualitative approach through interviews and observations to understand the experiences of female prisoners in prison. The research results show that the available health facilities do not support the reproductive and psychological health of female prisoners, who often face mental and emotional stress during their detention. These limitations have a negative impact on the welfare of female prisoners and demonstrate the need for correctional policies that are more sensitive to gender needs. It is hoped that these findings will encourage reform of the prison system to make it more inclusive, so that all prisoners, regardless of gender, receive fair treatment and adequate facilities.